SME steeplechase: When obtaining money is harder than innovating - M. Belén Guercio; Lisana B. Martínez; Aurelio Fernández Bariviera (International Journal of Financial Studies, 2019)
In this paper, we analyze the main characteristics of European Small and Medium Enterprises (SMEs), related to the demand for and access to external financial resources. We use microdata from an extensive database, elaborated by the European Central Bank and the European Commission: the Survey on the Access to Finance of Enterprises. Firstly, we consider a set of variables as determinants to the decision to apply for different financial instruments. Secondly, we use the same set of variables to analyze the actual access to these instruments. For each regression, several SMEs profiles were created, in order to detect SMEs archetypes according to their decisions. The results are thought-provoking, and highlight that differences in firms characteristics (size, innovative activities, etc.), influence not only the access to, but also the demand for external finance
Keywords: G21; G28; O3; O52; 330; financial decisions; innovative firms; EU; SME